Students' perception on the use of Gamestolearnenglish.com as a tool for grammar learning at SMP 2 Panti - Asyfa, Sandra; Rani, Yati Aisya (Journal of English Language Teaching, 2025)
This study aimed to investigate students' perceptions of using the Website Gamestolearnenglish.com as a tool for grammar learning, specifically focusing on the past tense, comparatives, adverbs, and future tense topics. The research employed a quantitative descriptive design using a survey method. The participants were 58 eighth-grade students from SMPN 2 Panti, who were selected through cluster sampling. Data were collected through a closed-ended questionnaire based on the extended Technology Acceptance Model (TAM) framework, which measured five key constructs: Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Hedonic Motivation (HM), Attitude Toward Use (ATU), and Behavioural Intention (BI). The results indicated that students' perceptions were positive across all five TAM constructs, with an overall mean score of 2.85. Findings revealed that students found the website useful, efficient, and effective for improving their grammar performance. They also perceived the website as easy to use and understandable. Additionally, students found learning the four grammar topics using this website fun and entertaining. Consequently, these positive perceptions led to favourable attitudes toward using the website and strong intentions to continue using it for grammar learning. These findings suggest that Gamestolearnenglish.com is a promising supplementary learning tool that enhances grammar mastery for junior high students. The study recommends integrating Gamestolearnenglish.com into English language learning to enhance students’ grammar outcomes